Arah dan Kepastian Hukum Terhadap Warga Kampung Bayam Demi Terciptanya Keadilan - Faturohman Faturohman; Mohamad Dian Ferriawan; Wahyu Setiaji (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Provisions that protect human freedom in the continuation of their lives, as well as obtaining adequate housing, especially in maintaining what has belonged to them from the start. In the case of residential evictions in the Kampung Bayam area, legal protection for human rights has not been realized to date. The evictions carried out by the DKI Jakarta Government were carried out arbitrarily without considering the impact on residents who lost their homes and also as a form of deprivation of the economic, social and cultural (ekosob) rights of the people of Kampung Bayam. Apart from that, until now too There is no real effort yet to be seen from the government to try to restore the housing rights of the residents of Kampung Bayam. Moreover, Indonesia is a country based on the supremacy of law, which means that Indonesia should make protection and respect for human rights its main focus.